Prenatal Hypoxia in Different Periods of Embryogenesis Differentially Affects Cell Migration, Neuronal Plasticity, and Rat Behavior in Postnatal Ontogenesis - Vasilev, Dmitrii S.; Dubrovskaya, Nadezhda M.; Tumanova, Natalia L.; Zhuravin, Igor A. (Frontiers in Neuroscience, 2016)
Long-term effects of prenatal hypoxia on embryonic days E14 or E18 on the number, type and localization of cortical neurons, density of labile synaptopodin-positive dendritic spines and parietal cortex-dependent behavioral tasks were examined in the postnatal ontogenesis of rats. An injection of 5’ethynyl-2’deoxyuridine to pregnant rats was used to label neurons generated on E14 or E18 in the fetuses. In control rat pups a majority of cells labeled on E14 were localized in the lower cortical layers V-VI while the cells labeled on E18 were mainly found in the superficial cortical layers II-III. It was shown that hypoxia both on E14 and E18 results in disruption of neuroblast generation and migration but affects different cell populations. In rat pups subjected to hypoxia on E14, the total number of labeled cells in the parietal cortex was decreased while the number of labeled neurons scattered within the superficial cortical layers was increased. In rat pups subjected to hypoxia on E18, the total number of labeled cells in the parietal cortex was also decreased but the number of scattered labeled neurons was higher in the lower cortical layers. It can be suggested that prenatal hypoxia both on E14 and E18 causes a disruption in neuroblast migration but with a different outcome. Only in rats subjected to hypoxia on E14 did we observe a reduction in the total number of pyramidal cortical neurons and the density of labile synaptopodin-positive dendritic spines in the molecular cortical layer during the first month after birth which affected development of the cortical functions. As a result, rats subjected to hypoxia on E14, but not on E18, had impaired development of the whisker-placing reaction and reduced ability to learn reaching by a forepaw. The data obtained suggest that hypoxia on E14 in the period of generation of the cells, which later differentiate into the pyramidal cortical neurons of the V-VI layers and form cortical minicolumns, affects formation of cortical cytoarchitecture, neuronal plasticity and behavior in postnatal ontogenesis which testify to cortical dysfunction. Hypoxia on E18 does not significantly affect cortical structure and parietal cortex-dependent behavioral tasks.